If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7y = 63 Solving 2x + 7y = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 2x + 7y + -7y = 63 + -7y Combine like terms: 7y + -7y = 0 2x + 0 = 63 + -7y 2x = 63 + -7y Divide each side by '2'. x = 31.5 + -3.5y Simplifying x = 31.5 + -3.5y
| 4y+8a+8y-2a= | | 8z-4=2z+5 | | 3x+9=17-x | | (X-19)-(x+5)=0 | | 4(2x+3)=3x-13 | | 2y^2-3y=5 | | P=1+3q | | -3x-5=7-7x | | -17+19+19-(19-17)= | | X^3-7X^2+13X-2=0 | | 2.1x+45.2=3.2-8.4x+2.1 | | 6r^3+5r^2+2r=0 | | -1(6-c)+3(2c-7)=1 | | -2(3a-4b+6)+7a-3= | | 1/x=4/1 | | 16*h-4(5*h-7)=4 | | 2-7[5-(7y-6)]= | | 3(2x+4)=x+17 | | n+15=32 | | (2n-6)(n+2)=0 | | 6-2p=16 | | 40-65+20= | | 2y^4+3y^2=7y^3 | | 4d-5=2d+5 | | -8(2t+9)=-88 | | n-15=32 | | -17+19+19-(19-(-17))= | | 4-5k=-8-5k | | 8*a-3(2*a+5)=13 | | 6-y=3y+8 | | 4(f-3)=-16 | | 4=20n |